2007
DOI: 10.1590/s0034-72992007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação auditiva em alcoolistas abstêmios

Abstract: Al coholism is considered the most relevant addiction in the international arena and few investigations have examined the association between sensorineural hearing loss and alcohol abuse, with conflicting results. Aim: To analyze the effects of alcohol abuse on the auditory system of alcoholics in abstinence taking into account the duration of alcohol abuse and associated noise exposure. Method: our series comprehended 75 individuals, divided into two groups: trial and control. The audiological assessment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…Although the relationship between hearing loss and alcohol consumption is not yet well established, some authors suggest this association. (17)(18)(19) In conclusion, due to the great number of patients with permanent hearing loss in our sample, we suggest that patients undergoing antituberculosis treatment be submitted to auditory monitoring in order to confirm (or not) the findings of the present study.…”
Section: Resultssupporting
confidence: 57%
“…Although the relationship between hearing loss and alcohol consumption is not yet well established, some authors suggest this association. (17)(18)(19) In conclusion, due to the great number of patients with permanent hearing loss in our sample, we suggest that patients undergoing antituberculosis treatment be submitted to auditory monitoring in order to confirm (or not) the findings of the present study.…”
Section: Resultssupporting
confidence: 57%
“…Na literatura também se cita que fumantes e ex-fumantes estão mais predispostos a desenvolverem perda auditiva 22 e também que o consumo excessivo de álcool pode predispor a perda auditiva 20,21 . Neste presente estudo, estes fatores foram efetivamente associados à perda auditiva.…”
Section: Discussionunclassified
“…Some studies previously identified a significant relationship between alcohol use and hearing loss (21)(22)(23) . According to the medical history provided (Table 1), it was observed a greater tendency to alcohol ingestion among the patients of Case Group.…”
Section: Discussionmentioning
confidence: 99%